Colorado Residents' Familiarity, Aesthetic Evaluations, and Approval of Forest Management Practices. Issue 1 (15th December 2016) - Peterson, Courtney L.; Vaske, Jerry J.
Abstract : This article examined the influence of familiarity with and aesthetic evaluations of forest management practices on Colorado residents' ( n = 416) approval of nine different forest management practices. The nine practices were (1) forest restoration, (2) planting trees as windbreaks, (3) wildfire defensible space, (4) forest thinning, (5) clearcuts, (6) patch cuts, (7) prescribed fire, (8) fuelbreaks, and (9) reducing surface fuels. Regression analyses indicated that both aesthetic evaluations of and familiarity with the forest management practices increased Colorado residents' approval of the practices. Aesthetic evaluations, however, had a larger impact on approval than familiarity, except for creating wildfire defensible space, windbreaks, and fuelbreaks. These findings suggest that outreach messages should be designed to not only increase familiarity with forest management practices but also highlight the aesthetic benefits of forest management to increase approval of different practices. Management and Policy Implications: State forestry agencies often focus education efforts on increasing public familiarity with forest management practices. This article suggests that managers should also highlight the aesthetic benefits of forest management practices in outreach and education efforts to enhance approval of forest management actions. Although familiarity with forest management practices increased approval in this study, evaluations of aesthetic impacts had a larger influence on overall approval. Because scenery is often a primary reason for people moving into forested areas, educating forest landowners on the aesthetic benefits of sound forest management is imperative for increasing overall forest health. Access to this information will allow state forestry agencies to more effectively work with forest landowners, as well as residents in urban and community forests, to accomplish sound forest management. As approval of forest management practices increases, the likelihood of support for bills that provide funding for proper forest management increases, creating benefits such as clean air, clean water, and increased biodiversity for all Colorado residents. The most effective methods of communicating the aesthetic benefits of forest management practices remain a topic for future research.